Retirement Behavior of Working Couples in Norway. A Dynamic Programming Approach - Zhiyang Jia (Statistics Norway, Research Department, 2005)
This paper aims to provide an empirical analysis of the joint retire ment behavior of working couples in Norway. A dynamic programming model is speci.ed and estimated on micro data. The estimation results show that a model, which uses only measures of economic incentives: wages and pension benefits gives a satisfactory fit to the observed retirement pattern. The results also indicate that husbands have higher bargaining power within the household. A hypothetical policy simulation shows that by taxing pension bene.ts as wage income, the labor market participation of both husbands and wives will increase around 4 percentage points at age 65.
Keywords: J26; 330; Household Retirement; Dynamic Programming